Pengetahuan Dengan Sikap Ibu Hamil Tentang Pelayanan Obstetri Neonatal Emergencydasar (Poned) - Noviana Puspitasari; Christina Pernatun Kismoyo; Ida Rumawat Astuti (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2014)
Background: Obstetrics and neonatal services regional service provision is an attempt for the mother and newborn integrated in the form of EmOC in clinics level. The key to success of EmOC is the availability of health care personnel according to competencies, infrastructure, facilities and reliable management. In addition, the lack of knowledge and attitude of pregnant women can also affect the success of Clinics EmOC. It is necessary for the realization of any expectant mothers in obtaining good information about Service Clinics EmOC.Objectives: To find out the relationship of knowledge with pregnant mothers attitude about Basic Emergency Obstetric Neonatal Care (EmOC) in clinic Bantul I Sewon Year of 2013.Methods: Descriptive analytic Study with cross sectional method. The population was pregnant women who are visiting Clinic Bantul Sewon in period I January 1, 2013. The sampling technique used in this research is accidental sampling with 155 respondents.Results: Knowledge of pregnant women either 55.5% whereas the attitude of expectant mothers to positive 88,3%. Based on the results of the analysis of knowledge with the attitude of expectant mothers about the Health Ministry EmOC obtained results the value of χ ² count 56,246 > χ ² 5,991 table and p value 0.000. p < 0,05 so the hypothesis is accepted.Conclusion: There is a relationship of knowledge and attitude to pregnant women about EmOC in clinic Bantul I Sewon Year of 2013.